Cigarette Smoke and Inflammation: Role in Cerebral Aneurysm Formation and Rupture. (13th December 2012) - Chalouhi, Nohra; Ali, Muhammad S.; Starke, Robert M.; Jabbour, Pascal M.; Tjoumakaris, Stavropoula I.; Gonzalez, L. Fernando; Rosenwasser, Robert H.; Koch, Walter J.; Dumont, Aaron S.
Abstract : Smoking is an established risk factor for subarachnoid hemorrhage yet the underlying mechanisms are largely unknown. Recent data has implicated a role of inflammation in the development of cerebral aneurysms. Inflammation accompanying cigarette smoke exposure may thus be a critical pathway underlying the development, progression, and rupture of cerebral aneurysms. Various constituents of the inflammatory response appear to be involved including adhesion molecules, cytokines, reactive oxygen species, leukocytes, matrix metalloproteinases, and vascular smooth muscle cells. Characterization of the molecular basis of the inflammatory response accompanying cigarette smoke exposure will provide a rational approach for future targeted therapy. In this paper, we review the current body of knowledge implicating cigarette smoke-induced inflammation in cerebral aneurysm formation/rupture and attempt to highlight important avenues for future investigation.